2015
DOI: 10.1016/j.jff.2015.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Naringin mitigate okadaic acid-induced cognitive impairment in an experimental paradigm of Alzheimer's disease

Abstract: Available online A B S T R A C TOkadaic acid (OKA), a selective and potent inhibitor of serine/threonine phosphatases 1 and 2A, induces hyper-phosphorylation of tau and thus has emerged as an effective tool to develop AD like pathology in animals. In the present study, we investigated the effect of naringin, against ICV-OKA-induced cognitive impairment as assessed by Morris water maze task which was accompanied by significantly enhanced oxidative-nitrosative stress, TNF-α, TGF-β, NF-κB, caspase-3 and IL-1β lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 48 publications
(49 reference statements)
0
16
0
Order By: Relevance
“…We found changes in the locomotor function and body weight, and reduced blood glucose level under the hydrogel-based drug treatment Gal compared with ICV-STZ-treated rats ( Demattos et al., 2012 ). These results indicate that hydrogel had positive effects on the body weight and control of the blood glucose level, which are key factors that affect the development of cognitive skills, such as memory and the learning efficiency in rats ( Butterfield et al., 2007 ; Sachdeva and Chopra, 2015 ). Cognitive tests comprising MWM, PA, and Y-maze tests demonstrated that hydrogel-based Gal administration improved the behavioral and cognitive activities.…”
Section: Discussionmentioning
confidence: 83%
“…We found changes in the locomotor function and body weight, and reduced blood glucose level under the hydrogel-based drug treatment Gal compared with ICV-STZ-treated rats ( Demattos et al., 2012 ). These results indicate that hydrogel had positive effects on the body weight and control of the blood glucose level, which are key factors that affect the development of cognitive skills, such as memory and the learning efficiency in rats ( Butterfield et al., 2007 ; Sachdeva and Chopra, 2015 ). Cognitive tests comprising MWM, PA, and Y-maze tests demonstrated that hydrogel-based Gal administration improved the behavioral and cognitive activities.…”
Section: Discussionmentioning
confidence: 83%
“…The total oxidants content is commonly assessed by the DCFH, and together with the antioxidant enzymes activity and GSH levels, they can demonstrate the redox status of a cell or tissue, thereby suggesting that in our model, with exception of the cerebellum, the maternal naringin supplementation triggered an antioxidant milieu in the pup’s brain regions on postnatal day 1 [ 52 ]. Accordingly, evidence elsewhere has also demonstrated that naringin supplementation can positively modulate the redox status in adult rat’s brains, improving antioxidants defenses and reducing the oxidants content, though it occurred with more than one week of naringin intake [ 34 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, even though naringin induced a prooxidative effect in the pups’ cerebellum and striatum, such alterations were not observed in the prefrontal cortex and hippocampus on postnatal 7 since these brain regions exhibited a positive modulation of the redox status. As shown in Table 1 , maternal naringin supplementation reduced the GSH content in the offspring’s prefrontal cortex in both sexes, but the male pups also displayed higher SOD and GPx activities, which has been demonstrated in adult male rats’ cerebral cortex in a dose-dependent manner [ 54 ]. Similarly, the pups’ hippocampal antioxidant enzymes were positively modulated while the GSH content was reduced on postnatal day 7.…”
Section: Discussionmentioning
confidence: 99%
“…Citrus flavonoids have been investigated for their effects on cognitive functions in different animal models. The citrus flavanone naringenin given orally to rats for 14 days improved spatial memory impairments, lipid peroxidation and oxidative stress induced by intracerebroventricular okadaic acid, and it decreased TNF‐α, TNF‐β, IL‐1, NF‐κB, and caspase‐3 activation (Sachdeva & Chopra, ). The hexamethoxyflavone nobiletin enhanced memory and reduced tau hyperphosphorylation and oxidative stress in the hippocampal tissue of senescence‐accelerated mice (SAM) after intraperitoneal administration for 40 days (Nakajima et al, ) and when administered by the same route for 3 months to mice (AD model), memory was improved and oxidative stress was reduced, although no effect on brain Aβ levels was observed (Nakajima et al, ).…”
Section: Phytochemicals As Nutraceuticalsmentioning
confidence: 99%
“…‐Naringenin improves spatial memory impairments, lipid peroxidation, and oxidative stress and decreases TNF‐α, TNF‐β, IL‐1, NF‐κB and caspase‐3 activation (Sachdeva & Chopra, )…”
Section: Phytochemicals As Nutraceuticalsmentioning
confidence: 99%